2008
DOI: 10.1364/oe.16.005757
|View full text |Cite
|
Sign up to set email alerts
|

Electric events synchronized with laser filaments in thunderclouds

Abstract: Abstract:We investigated the possibility to trigger real-scale lightning using ionized filaments generated by ultrashort laser pulses in the atmosphere. Under conditions of high electric field during two thunderstorms, we observed a statistically significant number of electric events synchronized with the laser pulses, at the location of the filaments. This observation suggests that corona discharges may have been triggered by filaments. R. Fieux, C. Gary, and P. Hubert, "Artificially Triggered Lightning above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 31 publications
2
93
0
Order By: Relevance
“…Typically, discharges are hundreds of meters in length, transfer up to 0.1-0.5 C per event, produce local electric fields in the order of several kVm -1 , typically release about 10 6 J, and seem to begin about 20 min after the eruptions vigorous initiation (Anderson et al, 1965;Brook et at., 1974;Katahira, 1992;McNutt and Davis, 2000). The geometric-mean peak currents of either polarity related to volcano lightning were sometimes only a factor of 2-3 lower than those associated to ordinary lightning recorded by the same network.…”
Section: Sources Within the Cavitymentioning
confidence: 89%
See 1 more Smart Citation
“…Typically, discharges are hundreds of meters in length, transfer up to 0.1-0.5 C per event, produce local electric fields in the order of several kVm -1 , typically release about 10 6 J, and seem to begin about 20 min after the eruptions vigorous initiation (Anderson et al, 1965;Brook et at., 1974;Katahira, 1992;McNutt and Davis, 2000). The geometric-mean peak currents of either polarity related to volcano lightning were sometimes only a factor of 2-3 lower than those associated to ordinary lightning recorded by the same network.…”
Section: Sources Within the Cavitymentioning
confidence: 89%
“…The laser pulse creates a channel of ionized gas through which the lightning stroke would be conducted to the ground. Under conditions of high electric field during two thunderstorms, Kasparian et al, 2008 observed a statistically significant number of electric events synchronized with laser pulses, at the location of the filaments. Laser-triggered lightning is intended to protect rocket launching pads, electric power facilities, airports, and other sensitive targets.…”
Section: Sources Within the Cavitymentioning
confidence: 90%
“…The weakly ionized plasma column and subsequent low density channel generated by laser filaments allow the precise triggering and guiding of electric discharges between two electrodes with a significant reduction of the breakdown voltage [7][8][9] . This effect is potentially useful for the development of laser lightning rod 4,[10][11] , high-voltage, high-current switches 12 , or virtual plasma antennas [13][14] .…”
mentioning
confidence: 99%
“…During femtosecond laser FIL in air, many nonlinear effects occur simultaneously, such as intensity clamping, molecular alignment, harmonic generation, self-phase modulation and so on [3][4][5] . These complex and interesting nonlinear phenomena accompanying femtosecond laser FIL lead to promising applications in different fields, such as remote sensing [6,7] , few-cycle pulse compression [8] , atmospheric condensation and precipitation [9][10][11] , secondary light source generation ranging from air lasing to terahertz emission [12][13][14][15][16][17][18] , and triggering and guiding high-voltage discharge with possible applications in lightning control [19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using a laser filament to couple the external electromagnetic fields and initiate the high-voltage discharge [32] has been successfully demonstrated [33] . Although there are many experimental contributions on filament-guided discharges [19][20][21][22][23][32][33][34][35][36] , investigations on how a laser filament guides the external high-voltage corona discharge (CD) had not been fully explored yet until recently, when we reported on a direct observation of laser-filament-guided CDs [37] . When a laser filament was generated at ∼1 mm from the tip of a copper electrode, as shown in Figure 1(a), a high DC voltage of 50 kV could be guided along the laser filament, forming blue CDs on both ends of the filament.…”
Section: Introductionmentioning
confidence: 99%